2006
DOI: 10.1038/sj.cdd.4401892
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the role of caspases during Drosophila oogenesis

Abstract: Cell death is a prominent feature of animal germline development. In Drosophila, the death of 15 nurse cells is linked to the development of each oocyte. In addition, females respond to poor environmental conditions by inducing egg chamber death prior to yolk uptake by the oocyte. To study these two forms of cell death, we analyzed caspase activity in the germline by expressing a transgene encoding a caspase cleavage site flanked by cyan fluorescent protein and yellow fluorescent protein. When expressed in ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 39 publications
5
91
0
1
Order By: Relevance
“…This may occur through the autoubiquitination of DIAP1 via its RING domain acting as a ubiquitin ligase. 27 Overexpression of diap1 or p35 resulted in defective egg chambers during mid-oogenesis (Figure 2b) as reported previously, 24,25 resembling dcp-1 mutants. 3 The overexpression lines displayed 93-100% defective mid-stage egg chambers, while control ovaries contained only 2% defective egg chambers (Table 1).…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…This may occur through the autoubiquitination of DIAP1 via its RING domain acting as a ubiquitin ligase. 27 Overexpression of diap1 or p35 resulted in defective egg chambers during mid-oogenesis (Figure 2b) as reported previously, 24,25 resembling dcp-1 mutants. 3 The overexpression lines displayed 93-100% defective mid-stage egg chambers, while control ovaries contained only 2% defective egg chambers (Table 1).…”
Section: Resultssupporting
confidence: 59%
“…18 Although caspases are expressed at high levels just before nurse cell death, [19][20][21][22][23] studies utilizing caspase reporters and inhibitors suggest that they do not play a role in developmental PCD. 24,25 Caspase-3 activity is extremely high throughout egg chambers undergoing mid-oogenesis degeneration. 24 We have previously shown that the effector caspase dcp-1 is essential for germline PCD in mid-oogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the destruction of egg chambers can be induced, most often at the midstages. Nutritional withdrawal results in both halted production and mid-stage destruction (Mazzalupo and Cooley, 2006), while RAP ingestion only results in midstage destruction ). In our current study, we found that, like RAP ingestion, FHV infection permitted the production of new egg chambers as measured by mitotic events in early egg chambers (P-HH3; Fig.…”
Section: The Ovarian Response To Systemic Infection With Flock House mentioning
confidence: 99%
“…For example, both mammalian ovarian follicles and insect egg chambers degenerate when specific apoptotic (Mazzalupo and Cooley, 2006;Nezis et al, 2002;Peterson et al, 2003;Tilly, 1998), autophagic (Escobar et al, 2008;Hou et al, 2008;Lobascio et al, 2007;Nezis et al, 2009Nezis et al, , 2010, and chromatin-degrading (Bass et al, 2009) pathways are activated. Moreover, complete degeneration and oocyte ''corpse'' removal is achieved by the phagocytosis of adjacent dead and dying cells by follicle cells in insects (Mazzalupo and Cooley, 2006) and granulosa cells in mammals (Inoue et al, 2000). The fly therefore may be increasingly used to study the comparative features of oocyte loss and the evolutionarily conserved genetic requirements of the process.…”
Section: Introductionmentioning
confidence: 99%